Commercializing science: nineteenth- and twentieth-century academic scientists as consultants, patentees, and entrepreneurs. (2nd January 2017) - Mercelis, Joris; Galvez-Behar, Gabriel; Guagnini, Anna
Abstract: The collection of essays introduced in this article contributes to the debate on the commercialization of academic science by shifting the focus from institutional developments meant to foster university technology transfer to the actions of individual scientists. Instead of searching for the origins of the 'entrepreneurial university, ' this special issue examines the personal involvement of academic physicists, engineers, photographic scientists, and molecular biologists in three types of commercial activity: consulting, patenting, and full-blown business entrepreneurship. The authors investigate how this diverse group of teachers and researchers perceived their institutional and professional environments, their career prospects, the commercial value of their knowledge and reputation, and their ability to exploit these assets. By documenting academic scientists' response to market opportunities, the articles suggest that, already in the decades around 1900, commercial work was widespread and, in some cases, integral to academics' teaching and research activity.